2016
DOI: 10.1242/dmm.024380
|View full text |Cite
|
Sign up to set email alerts
|

Loss ofvhlin the zebrafish pronephros recapitulates early stages of human clear cell renal cell carcinoma

Abstract: Patients with von Hippel–Lindau (VHL) disease harbor a germline mutation in the VHL gene leading to the development of several tumor types including clear cell renal cell carcinoma (ccRCC). In addition, the VHL gene is inactivated in over 90% of sporadic ccRCC cases. ‘Clear cell’ tumors contain large, proliferating cells with ‘clear cytoplasm’, and a reduced number of cilia. VHL inactivation leads to the stabilization of hypoxia inducible factors 1a and 2a [HIF1a and HIF2a (HIF2a is also known as EPAS1)] with … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
13
0
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(15 citation statements)
references
References 54 publications
0
13
0
1
Order By: Relevance
“…We have previously shown that zebrafish mutant in the VHL tumour suppressor develop key aspects of the human disease condition, including the activation of the HIF signalling pathway, the development of polycythemia and excessive neovascularization of the retina and brain, and recently, the loss of vhl was also shown to recapitulate ccRCC characteristics in zebrafish [29]. Here we report that vhl is required to maintain pronephric tubule and glomerulus integrity in zebrafish embryos.…”
Section: Introductionmentioning
confidence: 60%
“…We have previously shown that zebrafish mutant in the VHL tumour suppressor develop key aspects of the human disease condition, including the activation of the HIF signalling pathway, the development of polycythemia and excessive neovascularization of the retina and brain, and recently, the loss of vhl was also shown to recapitulate ccRCC characteristics in zebrafish [29]. Here we report that vhl is required to maintain pronephric tubule and glomerulus integrity in zebrafish embryos.…”
Section: Introductionmentioning
confidence: 60%
“…Renal cancer cells devoid of active pVHL are cilia deficient [156], while re-expression of pVHL in RCC cells restores cilia in a manner dependent on HIF-1α degradation [157]. The VHL-mediated control of cilia formation is evolutionary conserved as vhl −/− zebrafish mutants develop disorganized proximal pronephric tubules with disordered cilia [158]. Furthermore, pVHL protects microtubules from depolimerization in vivo [157] and pVHL-mediated stabilization of the axoneme microtubules is attenuated by GSK3β-mediated phosphorylation [159].…”
Section: Relevance Of Ciliary Genes In Renal Cancermentioning
confidence: 99%
“…Given the diversity of response, predictive biomarkers, such as HIF-2α and p53, may be useful for effective, targeted treatment. In zebrafish, treatment of vhl −/− embryos with a specific HIF2α inhibitor rescued pronephric abnormalities similar to human precancerous disease ( 38 ).…”
Section: Therapeutic Targets and Future Trialsmentioning
confidence: 99%
“…Likewise in zebrafish embryos, homozygous inactivation of VHL ( vhl −/− ) results in a kidney with enlarged proximal pronephric tubules, disorganized cilia, accumulated lipid and glycogen, cell proliferation, and apoptosis. This phenotype was rescued by a specific HIF2α inhibitor, showing that the zebrafish model system could be used to facilitate rapid screening of candidate drugs ( 38 ).…”
Section: Preclinical Modelsmentioning
confidence: 99%